Designing the Well-Being of Romanians by Achieving Mental Health with Digital Methods and Public Health Promotion - Brătucu, Gabriel; Tudor, Andra Ioana Maria; Litră, Adriana Veronica; Nichifor, Eliza; Chițu, Ioana Bianca; Brătucu, Tamara-Oana (International journal of environmental research and public health, 2022)
Taking care of mental health is a state of mind. Amid the challenges of the current context, mental health has become one of the problems with the greatest impact on citizens and the evolution of any economy. Due to the COVID-19 pandemic, people have become more anxious, solitary, preoccupied with themselves, and depressed because their entire universe has changed, by restricting their social and professional life; the increase in concern caused by a possible illness of them or those close to them made to isolate themselves. Two qualitative (group and in-depth interviews) and one survey-based quantitative research were carried out, which allowed the quantification of the opinions, perceptions, and attitudes of Romanians regarding the effectiveness of policies for the prevention and treatment of depression. Quantitative research revealed that most of the subjects had never participated in a mental health assessment, and a quarter of them had visited a mental health specialist more than two years ago. Based on the results, proposals were elaborated, which have been addressed both to the specialists from the Ministry of Health and to those from the academic environment, that may have an impact on the elaboration of some public mental health programs.